Simultaneous determination of deuterium-labeled ergosterol and brassicasterol in stroke-prone spontaneously hypertensive rats by ultra-high performance liquid chromatography-electrospray ionization-tandem mass spectrometry. Issue 46 (23rd November 2022) - Machida, Koichi; Koseki, Yuji; Kotani, Akira; Yamamoto, Kazuhiro; Miura, Tsuyoshi; Hakamata, Hideki
Abstract : A highly sensitive LC-MS/MS method disclosed that deuterium-labeled brassicasterol in serum was increased in a time-dependent manner, when deuterium-labeled ergosterol was orally administrated to stroke-prone spontaneously hypertensive rats. Abstract : A previous study has shown that brassicasterol- d 1 was detected in the serum of stroke-prone spontaneously hypertensive rats after oral administration of ergosterol- d 1 . To quantitatively evaluate the serum concentration of brassicasterol- d 1, an ultra-high performance liquid chromatography-electrospray ionization-tandem mass spectrometry method was developed for the simultaneous determination of picolinyl ester-derivatized ergosterol- d 1 and brassicasterol- d 1 . The separation was performed on an ODS column (Waters Acquity UPLC BEH C18) with a mobile phase consisting of methanol and water containing 0.1% acetic acid (95/5, v/v). Linear calibration curves in the presence of the serum were obtained in a concentration range of 0.04–8 μg mL −1 . Recovery rates of 95.6–119% were obtained with an RSD ( n = 6) of less than 7.5%. The method was applied to the determination of time-concentration curves of ergosterol- d 1 and brassicasterol- d 1 in stroke-prone spontaneously hypertensive rats, showing a pharmacokinetic profile of ergosterol- d 1 where the peak serum concentration of brassicasterol- d 1 was 3-fold higher than that of ergosterol- d 1 .